Wake up missing - Messner, Kate (Bloomsbury, 2014)
When four teens with similar head injuries wind up in a brain-science center in the Florida Everglades, they believe they are receiving treatment that will return their lives to normal. It soon becomes apparent that a top-secret experiment is changing them in unforeseen ways, and they must work together to escape the facility lest they lose themselves for good.